A novel antidepressant mechanism of baicalin: enhancing KIF5A-mediated axoplasmic transport and vesicular trafficking in glutamatergic neurons - Lu, Shuaifei; Shen, Jiduo; Jin, Xiaohui; Zhang, Changjing; Wang, Baoying; Liu, Xianghua; Bai, Ming; Xu, Erping; Yan, Xiangli; Li, Yucheng (Frontiers in Pharmacology, 2025)
IntroductionDysfunction of axoplasmic transport is closely linked to depression. Baicalin, a major flavonoid in Scutellaria baicalensis, a well-known traditional Chinese medicine used in depression treatment, has demonstrated antidepressant-like effects in previous studies. However, its potential role in regulating axoplasmic transport has not been explored. This study aims to investigate the antidepressant mechanisms of baicalin through modulation of axoplasmic transport in hippocampal neurons.MethodsMale C57BL/6N mice were exposed to chronic unpredictable mild stress (CUMS) and treated with baicalin (10, 20, 40 mg/kg) or fluoxetine (20 mg/kg). Depression-like behaviors were assessed using the sucrose preference test (SPT), forced swimming test (FST), tail suspension test (TST), and locomotor activity test (LAT). Hippocampal neuronal pathology was examined using transmission electron microscopy (TEM), Nissl, and Golgi staining. Transcriptomic analysis was conducted to explore the molecular mechanisms of baicalin. HT22 cells were cultured in vitro and treated with corticosterone (CORT) and baicalin. FM1-43 was used to label vesicles and track vesicular movement. mRNA and protein levels were measured by qRT-PCR, Western blotting, and immunofluorescence.ResultsBaicalin significantly alleviated CUMS-induced depressive behaviors, increasing sucrose preference, reducing immobility time in TST and FST, and increasing food intake without affecting locomotor activity. It improved hippocampal CA3 neuronal damage, increased dendritic spine density, and promoted presynaptic vesicle accumulation, particularly in glutamatergic neurons. Transcriptomic analysis revealed that baicalin upregulated vGLUT2 (encoded by the Slc17a6 gene) and significantly increased the expression of GluN2B, GluA1, and PSD95. Moreover, baicalin upregulated the expression of kinesin family member 5A (KIF5A) both in vivo and in vitro, enhancing vesicle movement along axons and increasing vesicle-associated membrane protein 2 (VAMP2) enrichment in synaptosomes.DiscussionThese findings suggest that baicalin enhances anterograde axoplasmic transport by upregulating KIF5A expression, facilitating vesicular trafficking and improving synaptic function in glutamatergic neurons. This study provides novel insights into the molecular mechanisms of antidepressant effects of baicalin, highlighting KIF5A as a potential therapeutic target for depression.